FRI0328 A Complete Remission Lasting at Least One Year Influences The Outcome in Patients Affected by SLE: Results from A Large Monocentric Cohort. (15th July 2016) - Ceccarelli, F.; Cipriano, E.; Perricone, C.; Leccese, I.; Massaro, L.; Miranda, F.; Morello, F.; Pacucci, V.; Orefice, V.; Pendolino, M.; Pirone, C.; Spinelli, F.R.; et al.
Abstract : Background: The achievement of complete remission is one of the most important goal in the management of patients with Systemic Lupus Erythematosus (SLE). Even though a definition of remission has been proposed (complete absence of any clinical and serological sign or symptom of activity) and the concomitant acceptable treatment (including antimalarial drugs only) has been identified, however the minimum lapse of time is still controversial. This issue is of primary importance in a disease characterized by a relapsing-remitting course. Several cut-off have been suggested, ranging from 1 to 5 years. Objectives: The primary end-point of the present study was to analyze the frequency of complete remission lasting at least 1 year in a large monocentric SLE cohort. Furthermore, we aimed at evaluating its association with different clinical and serological parameters and its impact on the chronic damage accrual. Methods: Data on Caucasian SLE patients, diagnosed according to the ACR Classification Criteria for SLE, were collected. We included in the present analysis SLE patients evaluated at least twice per year during the last 5 years. The frequency of complete remission, defined as an SLE Disease Activity Index 2000 (SLEDAI-2k) =0, was assessed in glucocorticoid-free and immunosuppressant-free patients. Antimalarial drugs were the only SLE-related acceptable treatment. Results: Our database includes 658 SLE patients evaluated at least once. From these patients non-Caucasian were excluded, resulting in 622 patients. Among these, 179 (M/F 13/166, mean age 46.3±12.7 years, mean disease duration 173.9±101.9 months) fulfilled the above-reported selection criteria. During the 5-year follow-up, 27 patients (15.1%) experienced a complete remission lasting for at least 1 year, with a mean duration of 37.5±15.8 months. Notably, six patients experienced a prolonged complete remission lasting 5 years (4.6%). There were no significant differences in terms of demographic characteristics between patients achieving and those not achieving remission. Patients in remission showed a significantly lower frequency of renal involvement (29.0 vs 18.4, P=0.04) and low C3 and C4 (14.8% vs 36.8%, P=0.0005; 14.8% vs 33.5%, P=0.0002, respectively). There were no other differences in terms of clinical and laboratory features. The frequency and the severity of chronic damage, evaluated by SLICC Damage Index (SDI), resulted significantly lower in patients achieving remission (11.1% vs 51.9%, P<0.000001; 0.48±0.8 vs 0.8±1.2, P=0.03, respectively). The length of the remission status did not influence the chronic damage. At the multivariate analysis, no independent factors were associated with remission; conversely, low C3 resulted a risk factor for absence of remission (OR=0.15, 95% CI 0.03–0.06). Conclusions: In the present SLE cohort, a complete remission lasting at least 1 year has been identified in 15% of patients. The remission status, regardless of its duration, is associated with a lower chronic damage, in terms of frequency and severity. These results suggest that the achievement of a state of remission lasting at least one year may represent a favorable prognostic factor in patients with SLE. Disclosure of Interest: None declared